Case report: Slipped capital femoral epiphysis: a rare adverse event associated with FGFR tyrosine kinase inhibitor therapy in a child - Brizini, Meziane; Drimes, Tina; Bourne, Catherine; Streilein, Jessica; Drapeau, Annie; Wrogemann, Jens; Archer, Lori Anne; Del Bigio, Marc; Vanan, Magimairajan Issai (Frontiers in Oncology, 2024)
We report a case of Slipped Capital Femoral Epiphysis (SCFE), an on target skeletal toxicity of a pan-FGFR TKI inhibitor, erdafitinib. A 13-year-old boy was diagnosed to have an optic pathway / hypothalamic glioma with signs of increased intracranial pressure and obstructive hydrocephalus requiring placement of ventriculo-peritoneal (VP) shunt. Sequencing of the tumor showed FGFR1-Tyrosine kinase domain internal tandem duplication (FGFR1-KD-ITD). He developed hypothalamic obesity with rapid weight gain and BMI >30. At 12 weeks of treatment with erdafitinib, he developed persistent knee pain. X-ray of the right hip showed SCFE. Erdafitinib was discontinued and he underwent surgical pinning of the right hip. MRI at discontinuation of erdafitinib showed a 30% decrease in the size of the tumor, which has remained stable at 6 months follow up. Our experience and literature review suggest that pediatric patients who are treated with pan-FGFR TKIs should be regularly monitored for skeletal side effects.